Culture Proven Bacterial Meningitis in Children: Agents, Clinical Profile and Outcome - Ansari, I; Pokhrel, Y (Kathmandu University Medical Journal, 2012)
Background Meningitis is a serious infection. Little is known about the bacterial agents and their antibacterial sensitivity in Nepalese children. Objectives To study bacteriological agents, clinical profile and immediate outcome in patients admitted to children’s ward of Patan Hospital with meningitis. Methods Prospective observational study conducted in paediatric ward of Patan Hospital. All the children admitted to the ward, with the diagnosis of culture proven bacterial meningitis’ on discharge were eligible. Results Out of 7,751 children, 296 (3.8%) had meningitis. This was a group ranging from neonates to adolescents aged 18 years. Only 13 (4.4%) of cerebrospinal fluid samples taken from them yielded positive culture reports. The organisms were pneumococcus (6), Haemophilus influenza ‘b’ (3), ?-hemolytic Streptococcus (1), ?-hemolytic Streptococcus (1), N. meningitides (1) and Pseudomonas (1). Whereas Haemophilus influenza ‘b’ was isolated from young infants, pneumococci were found in the young as well as the old. Fever, vomiting, high leukocyte count with left shift were all commonly present. All but one had cerebrospinal fluid pleocytosis. Low sugar and high protein was found in most specimens. Neuroimaging was done in six children of which three were abnormal (all young infants and pneumococci cases). Ceftriaxone was given to all but one child. Everybody recovered but three had complications – profound hearing loss and cortical atrophy with subdural collection in pneumococcal and septic arthritis with persistence of fever in Haemophilus influenzae ‘b’ meningitis. Conclusion The present study corroborates most of the epidemiological and clinical features of acute bacterial meningitis and sheds light on the causative agents of bacterial meningitis in Nepalese children. http://dx.doi.org/10.3126/kumj.v9i1.6260 Kathmandu Univ Med J 2011;9(1):36-40